ANALISIS DAN PEMETAAN NILAI AKSESIBILITAS HOTSPOT AREA DI KAMPUS MENDALO UNIVERSITAS JAMBI MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) - Edi Saputra; Mauladi Mauladi; Tri Sutrasno (Universitas Batanghari Jambi, 2017)
The high mobility of the user causing the use of wireless access media like hostspot(WiFi) to connect to the Internet is increasingly dominant. In order to support academic activities, almost all the buildings in the campus Mendalo University of Jambi (UNJA) already have a hotspot area. The effectiveness of the use of this hotspot is determined by the value of Aksesibilitasnya. The use of media access to the Internet said to be optimal if the value high and equitable hotspot accessibility. This study willanalyze and map the value of the existing area hotspot accessibility in Jambi University to find out whether the spread is as effective as a hotspot. The population in this study are all the hotspots run by the University of LPTIK Jambi by taking samples ofhotspot areas is LPTIK. The variable in this study is the point spread of a hotspot in the x and y coordinates; The signal strength of a hotspot; The number of user hotspot; total bandwidth used. The analysis of the Data used in this study is the analysis ofthe plotting and analysis of geographic information systems (GIS). This research will be produced from a geographic information system that provides information of hotspot deployment point with the value aksesibilitasnya.Keywords: Hotspot, the value of accessibility, geographic information systems